SEJARAH BERDIRINYA MASJID RAYA AN-NUR PROVINSI RIAU - Rian Febrisono; Ridwan Melay; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Mosque Raya An-Nur Riau Province is the largest and grandest mosque located in the center of Pekanbaru City, the shape of this building looks like architectural style of Arab Countries, Turkey, India and Malay. The influence of Malay culture appears on wooden pulp wood carving motifs located in mihrab The influence of Arab culture can be seen on the decorative elements of calligraphy written in the building Mosque Raya An-Nur Riau Province. Most people call this mosque building resembling the Taj Mahal in India. The construction of Mosque Raya An-Nur is the era of Riau Province Government led by Governor II Kaharudin Nasution in 1963, then completed the development is during the Riau Province governance led by Riau Governor III Arifin Ahmad, marked by the inauguration by Governor Arifin Ahmad On October 19 1968 with the signing of Inscription. After Shaleh Djasit was inaugurated as Governor of Riau in 1998. The management appealed to the Governor to renovate Masjid Raya An-Nur In line with the renovation activities, the various parts of existing facilities such as study rooms, towers built in 1990 overhauled and removed for erected buildings supporters on both sides of the Grand Mosque building of An-Nur Mosque with various facilities such as kindergarten, elementary school, and Bilal House and will be built more versatile multipurpose building. renovation activities of main building and supporting facilities began to be implemented since 2002 in Riau Province led by Riau Governor H. Saleh Djasit. Renovation activities completed in 2006 in Riau Province led by Riau Governor H. M. Rusli Zainal. Grand Mosque Building An-Nur Riau Province and its supporting facilities inaugurated by the President of the Republic of Indonesia Susilo Bambang Yudhoyono On August 11, 2007 with the golden anniversary of Riau Province to-20 in 2015 the name of the Grand Mosque changed into Mosque Raya An-Nur Riau Province.Key Words: History, Mosque, Riau